TAFSIR MAKNA NEGARA HUKUM DALAM PERSPEKTIF UNDANG-UNDANG DASAR NEGARA REPUBLIK INDONESIA TAHUN 1945 - Janpatar Simamora (Jurnal Dinamika Hukum, 2014)
According to Article 1 paragraph (3) of constitution 1945 stated that "Indonesia is a state of law". However, there was no explanation of the meaning a state of law by the constitution 1945. While, conception the state of law always refers to two different streams, namely state of law in meaning rechtsstaat and state of law within the meaning of the rule of law. To answer meaning of state of law by the constitution 1945, it is necessary to understand subtance "Preamble", in particular the fourth paragraph of about the goal of the state of Republic Indonesia.Keywords: state of law, Pancasila, Constitution 1945.